Water supply of Zaporizhzhya Priazovye: nascent, stages of development, problems of nowadays and hygienic substantiation of ways of their solutions. - K. Zagorodniuk; S. Omelchuk; Yu. Zagorodnyuk; P. Vanat; M. Nikulin; A. Grinzovskyy; O. Chyzhyk (Medičnì Perspektivi)
At the modern stage of development humanity is on the verge of the pandemic of non-communicable diseases. It is not an exception for the population of the Ukraine, among which more than 2/3 of the total morbidity incidences is non-communicable diseases: desieses of cardiovascular system, cancer, chronic respiratory diseases, diabetes. To the mind of experts in the field of public health and environment protection,the first place among factors affecting the level of population’s health in Ukraine is given to the water that is ahead of air and food products in this aspect. Taking into consideration the fact that after annexation of the Crimea by the Russian Federation in March of 2014and uncertainty in the military-political situation on the East of the Ukraine, Zaporizhzhya Priazovye is becoming a recreational zone, and with each year it will be used by more and more Ukrainian citizens.The objective of our research was to investigate nascent, stages of development and nowadays problems of region’s water supply as well as hygienic substantiation of complex ways of nowadays problem of Zaporizhzhya Priazovye water supply. As a result of conducted researches it was found that single economically feasible way of providing population of Zaporizhzhya Priazovye with water with normative total hardness and general mineralization is supply ofthe Dnipro water carried out by operation ofWestern group water conduit. To reduce the formation of chlorination by-products in the process of water purification it is necessary to use iron-containing chlorine-sulfate coagulant "Aula" of brand A according to the technical requirements TR U 24.1-33075701-002: 2011. For utilization of flush water of contact clarifiers, it is necessary to retool water purification facilities by clarifiers-recirculators with sediment recirculation in “inner contour”. It was proved that corrosive aggressiveness is an indicator of water quality which will determine further development of the group water conduits of Ukraine. At the same time it was established that stabilization and correction of water corrosive aggressiveness with chemical Sea-Quest allows to supply normative quality water through extended water supply systems to the end consumers, to significantly slow down the process of senescence, particularly in pipelines and in tanks of clean water as well.